More media-oriented than literacy-focused: Problematizations in Indonesia’s digital literacy policy - Harahap, Tamam Ruji; Mutmainnah, Nina; Irwansyah; Kurnia, Novi (Program Studi Ilmu Komunikasi, 2025)
This study aims to discuss the construction of the problem underlying the digital literacy policy in Indonesia. As policy communication research, this study considers the Ministry of Communication and Informatics (MOCI) digital literacy programs as policy-as-discourse. This study is qualitative and uses a desk-based method to collect the data. This study uses the “What’s the ‘problem’ represented to be” (WPR) analytical strategy to analyze the data. This study finds out that the MOCI constructs the digital literacy policy to be based on handling the massive spread of negative content and illegal activities on the internet and social media platforms. Therefore, this MOCI’s construction of knowledge on digitalliteracy is oriented more toward media issues than literacy issues in digital technologies. This study recommends that the knowledge construction on digital literacy policy is based not only on the problem of media criticality but also on addressing the problem of literacy in the utilization of digital technology for educational purposes.